The 13-Valent Pneumococcal Conjugate Vaccine Elicits Serological Response and Lasting Protection in Selected Patients With Primary Humoral Immunodeficiency - Robbins, Ailsa; Bahuaud, Mathilde; Hentzien, Maxime; Maestraggi, Quentin; Barbe, Coralie; Giusti, Delphine; Le Naour, Richard; Batteux, Frederic; Servettaz, Amélie (Frontiers in Immunology, 2021)
Background: Patients with primary humoral immunodeficiency are more prone to invasive as well as recurrent pneumococcal infections. Therefore, anti-pneumococcal vaccination including the 13-valent conjugate vaccine is recommended. Nevertheless, to date, no data is available on immunogenicity of this vaccine in this population. Objective: to assess the immunogenicity and the persistence of protection up to one year after a 13-valent pneumococcal conjugate vaccine in patients with primary humoral immunodeficiency. Methods: twenty-nine patients with common variable immunodeficiency or IgG subclass deficiency were vaccinated. Immune response and immune protection at baseline as well as at one, six and twelve months after vaccination were evaluated by measuring specific IgG serum concentrations (ELISA), and opsonophagocytic activities directed against selected pneumococcal (MOPA). Results: By ELISA, half of the patients had protective IgG concentrations before vaccination, 35.7% showed an immune response one month after vaccination, 71.4%, 66.7% and 56.0% of the patients were protected at one, six and twelve months respectively. Conversely, by MOPA, 3.4% of the patients were protected at baseline, 10.7% showed an immune response and 28.6%, 48.2% and 33.3% were protected at one, six and twelve months respectively. IgG subclass deficiency, Ig replacement therapy and higher IgG2 concentrations at diagnosis were associated with long-term protection. Conclusion Pneumococcal conjugate vaccine improves immune protection and antibodies’ functionality in a subset of patients with primary immunodeficiency. Prime-boost vaccine strategy needs to be better and individually adapted.